Lamotrigine for Absence Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The effectiveness and safety of lamotrigine (Lamictal) monotherapy in newly diagnosed typical absence seizures in 45 children and adolescents, aged 3-15 years, were evaluated in a placebo-controlled, double-blind trial at centers in Norfolk, VA; Akron, OH; Boston, MA; and Research Triangle Park, NC.